Topics and trends in fresh tea (Camellia sinensis) leaf research: A comprehensive bibliometric study - Chen, YiQin; Li, YunFei; Shen, ChengWen; Xiao, LiZheng (Frontiers in Plant Science, 2023)
Tea plant (Camellia sinensis) is a widely cultivated cash crop and tea is functional food in the world. Fresh tea leaves (FTLs) play a critical role in bridging the two fields closely related to tea cultivation and tea processing, those are, tea plant biology and tea biochemistry. To provide a comprehensively overviews of the development stages, authorship collaborations, research topics, and hotspots and their temporal evolution trends in the field of FTLs research, we conducted a bibliometric analysis, based on 971 publications on FTLs-related research published during 2001-2021 from Web of Science Core Collection. CiteSpace, R package Bibliometrix, and VOSviewer were employed in this research. The results revealed that the development history can be roughly divided into three stages, namely initial stage, slow development stage and rapid development stage. Agricultural & Food Chemistry published most articles in this field, while Frontiers in Plant Science holds the highest total citations and h-index. The most influential country, institution, and author in this field is identified as China, the Chinese Academy of Agricultural Sciences, and Xiaochun Wan, respectively. FTLs-related research can be categorized into three main topics: the regulation mechanism of key genes, the metabolism and features of essential compounds, and tea plants' growth and stress responses. The most concerning hotspots are the application of advanced technologies, essential metabolites, leaf color variants, and effective cultivation treatments. A shift from basic biochemical and enzymatic studies to multi-omics technology-dependent molecular mechanism studies were found. We also discussed the future development in this field. This study provides a comprehensive summary of the field, making it easier for researchers to be informed about its development history, status, and trends.